2014
DOI: 10.3168/jds.2013-7634
|View full text |Cite
|
Sign up to set email alerts
|

Effect of regrowth interval and a microbial inoculant on the fermentation profile and dry matter recovery of guinea grass silages

Abstract: The objectives of this study were to characterize and quantify the microbial populations in guinea grass (Panicum maximum Jacq. cultivar Mombasa) harvested at different regrowth intervals (35, 45, 55, and 65 d). The chemical composition and fermentation profile of silages (after 60 d) with or without the addition of a microbial inoculant were also analyzed. Before ensiling, samples of the plants were used for the isolation and identification of lactic acid bacteria (LAB) in the epiphytic microbiota. A 4 × 2 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 25 publications
4
28
2
1
Order By: Relevance
“…growth and ammonia production (Xing et al, 2009;Tian et al, 2014). INO treatments decreased acetate and butyrate concentrations and were consistent with the results of Santos et al (2014). Low pH values often imply an increased lactic acid production, which reduces the production of other VFA and proteolysis in the silo (Muck, 1996).…”
Section: Fermentative Profilesupporting
confidence: 70%
See 1 more Smart Citation
“…growth and ammonia production (Xing et al, 2009;Tian et al, 2014). INO treatments decreased acetate and butyrate concentrations and were consistent with the results of Santos et al (2014). Low pH values often imply an increased lactic acid production, which reduces the production of other VFA and proteolysis in the silo (Muck, 1996).…”
Section: Fermentative Profilesupporting
confidence: 70%
“…In the current study, INO addition decreased pH, linearly increased the amounts of lactic acid bacteria and linearly decreased counts of mould and yeast in the silage, which likely prevented secondary fermentation processes. Santos et al (2014) inoculated guinea grass with a mixture of homofermentative lactic acid bacteria (LAB; containing L. plantarum, P. acidilactici and Enterococcus faecium) and reported a decrease in gas losses with a consequent increase of silage DM recovery. In addition, a synergetic effect of ENZ and INO8 combination on gas losses was noticed.…”
Section: Fermentative Profilementioning
confidence: 99%
“…In terms of nutritional value, tropical grasses can be affected by their growth stage; therefore, maturity is considered the most important factor affecting the chemical composition and nutritional quality of forages (Ribeiro et al, 2014). The nutritional value of forages linearly declines with increasing physiological maturity (Santos et al, 2014). As observed in this study, the increase in DM content with increasing maturity was expected.…”
Section: Chemical Compositionsupporting
confidence: 67%
“…The DM content of forages is important in calculating feed intake and improving milk production, but it is also important when farmers are interested in conserving this resource (i.e., silages). A DM content of 25% is recommended for minimizing effluent loss in silos and the preservation of nutrients in silages (Santos et al, 2014). In this study, grasses showed similar DM contents, showing their suitability for silage conservation.…”
Section: Chemical Compositionsupporting
confidence: 52%
“…Grass silages can be improved by the use of other foods to increase the dry matter content and of compounds that favor fermentation and by the use of microbial inoculants (Santos et al, 2014;Brant et al, 2017).…”
Section: Chemical Composition Of Elephant Grass and Silage Producedmentioning
confidence: 99%